Respuesta :
For the answer to the question above,
The average rate of change = [f(1)-f(0)] /(1-0)
f(x) = -x^4+4x^3-2x^2+x+1
Then substitute it with the given value,
f(1) = -1+4-2+1+1 = 3
Then simplify and solve.
f(0) = 1
[f(1)-f(0)] /(1-0) = (3-1)/1 = 2I hope my answer helped you
The average rate of change = [f(1)-f(0)] /(1-0)
f(x) = -x^4+4x^3-2x^2+x+1
Then substitute it with the given value,
f(1) = -1+4-2+1+1 = 3
Then simplify and solve.
f(0) = 1
[f(1)-f(0)] /(1-0) = (3-1)/1 = 2I hope my answer helped you
Answer:
I believe the answer is (C.2)
Step-by-step explanation:
The answer isn’t 1. I took the test and ‘B’ is incorrect